Quality by Design for the Development and Analysis of Enhanced In-Situ Forming Vesicles for the Improvement of the Bioavailability of Fexofenadine HCl In Vitro and In Vivo - Ali M. Nasr; Mona K. Qushawy; Mahmoud M. Elkhoudary; Aya Y. Gawish; Sameh S. Elhady; Shady A. Swidan (MDPI AG, 2020)
Drug absorption from the gastrointestinal tract (GIT) is one of the major problems affecting the bioavailability of orally absorbed drugs. This work aims to enhance Fexofenadine HCl oral bioavailability in vivo, the drug used for allergic rhinitis. In this study, novel spray-dried lactose-based enhanced in situ forming vesicles were prepared using different absorption enhancer by the slurry method. Full factorial design was used to obtain an optimized formulation, while central composite design was used to develop economic, environment-friendly analysis method of Fexofenadine HCl in plasma of rabbits. The optimized formulation containing Capryol 90 as absorption enhancer has a mean particle size 202.6 ± 3.9 nm and zeta potential −31.6 ± 0.9 mV. It achieved high entrapment efficiency of the drug 73.7 ± 1.7% and rapid Q3h release reaches 71.5 ± 2.7%. The design-optimized HPLC assay method in rabbit plasma could separate Fexofenadine HCl from endogenous plasma compounds in less than 3.7 min. The pharmacokinetic study and the pharmacological effect of the fexofenadine-loaded optimized formulation showed a significant increase in blood concentration and significantly higher activity against compound 48/80 induced systemic anaphylaxis-like reactions in mice. Therefore, enhanced in situ forming vesicles were effective nanocarriers for the entrapment and delivery of Fexofenadine HCl.